Global trend and hotspot of resin materials for dental caries repair: a bibliometric analysis - Han, Baodi; Wang, Lian (Frontiers in Materials, 2024)
The objective of this study is to explore the current research status, key areas, and future development trends in the field of resin materials for dental caries repair through an objective and quantitative analysis of the literature. Methods: A search was conducted on the Web of Science Core Collection using "dental cavity" and "resin" as keywords, covering the period from 2000 to 2023. Data including author names, journals, countries, institutions, keywords, and citation rates were extracted. The collected data was subjected to statistical analysis using bibliometrics methodology, and visual knowledge maps were generated using software like CiteSpace 6.2.R4, Microsoft365, and R. Results: A total of 4800 articles were retrieved, involving 13,423 authors, 2654 institutions, 76 countries, and 560 journals. The number of publications and cumulative publications in this field showed an increasing trend, reaching a peak in 2022. Dental Materials was the journal with the highest number of publications, cumulative publications, and citation rates. XU HHK was the most prolific author in terms of publications and citations. The University of Maryland was the institution with the highest number of publications. Brazil was the country with the highest number of publications. The USA had the highest level of collaboration with other countries. Collaboration between different authors, institutions, and countries in this field was relatively close, which contributed to the rapid development of resin materials for caries repair. The current research focus is mainly on the nature of dental caries, characteristics of resin materials, and bonding strength of adhesives. Enhancing the bioactivity and remineralization of resin materials, advanced antibacterial strategies, longevity and durability of resin restorations, nanotechnology, and material innovation, as well as digital dentistry, will receive increased attention as future research trends. Conclusion: Resin materials for dental caries repair have received significant attention. Future research should combine nanotechnology and big data analysis to investigate the mechanisms of dental caries occurrence and development, enhance the performance and longevity of resin materials, and conduct high-quality, large-scale empirical research.